(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2021)
The study of the most used plants in the Jauneche Enclosure, Palenque Canton, Los Ríos Province, Ecuador, had the goal of knowing the local ethnobotany. To obtain the primary information three people with knowledge about useful plants were interviewed, with the data of the initial phase simple surveys were carried out on 20 people over 35 years old, a total of 84 useful plants were recorded. Once the information was obtained, the respective ethnobotanical classification was carried out, recording the following uses: medicinal, food, construction and rudimentary (homemade utensils). Medicinal plants were the most representative with 57%, followed by food plants with 26%, construction 13% and rudimentary 4%, the taxonomic identification based on collected samples yielded 37 families and 61 genera, the family with the largest number of species were Lamiaceae and Asteraceae. These results indicate that the use of useful plants in the Jauneche Enclosure could be regarded as high, because the gathered information was obtained from 23 people only, indicating that ethnobotanical knowledge is present in the inhabitants of the Jauneche enclosure, adducing this factor to the close relationship they maintain with the forest of the Pedro Franco Dávila Biological Station.